God and the Nation: Protestants, Patriotism and Pride in Cuba, 1890–1906. (1st April 2016) - James A. Baer
Abstract : The career of Evaristo Collazo demonstrates the nuanced aspects of Cuban-American relations within the Protestant community at a critical moment in the history of Cuba at the end of the nineteenth and beginning of the twentieth century. US influence on the Cuban political system and economy is well documented. The significance of Protestant activity in Cuba is less studied but often conforms to the notion of US hegemony. Collazo and other Cuban Protestant pastors operated in an environment strongly influenced by US teachings and values. Nevertheless, they responded in ways that suggest Cubans found some space for leadership and authority within a transnational bond of religion. This study of Collazo and the Presbyterian Church in Cuba provides a deeper understanding of the importance of transnational approaches to issues that transcend national boundaries and offers a clearer picture of the ways Cubans reacted to and resisted US hegemony.